PEMBINAAN KESOPANAN ANAK MELALUI KOMUNIKASI PERSUASIF ORANG TUA DI KELURAHAN PAMPANG MAKASSAR - Haruna, Rahmawati; Purnama, Hardianti (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2020)
This study discusses the development of child courtesy through persuasive communication of parents in Kelurahan Pampang Makassar which aims to answer the research question, what is the form of persuasive parental communication towards the development of child decency in Pampang District of Makassar City and what are the factors inhibiting parental persuasive communication towards fostering child politeness in Pampang Urban Village Makassar? This type of research is classified as a qualitative descriptive study with research subjects are parents, children, and community members. Data collection methods by observation, interview, and documentation. The results showed that (1) Persuasive communication that is applied in fostering child politeness is the exemplary method and the habituation method. (2) The inhibiting factors are the parents' busyness and the influence of the environment outside the home.